Liquid crystal polyester resin, molded article, and electrical / electronic component

By using high-content aromatic hydroxycarboxylic acid structural units in liquid crystal polyester resins, the composition ratio is adjusted, and the problem of insufficient dielectric loss tangent and dimensional stability under high-frequency band signals is solved, and low dielectric loss tangent and dimensional stability is achieved A resin with excellent properties, suitable for high-frequency electronic equipment.

CN119256038APending Publication Date: 2025-01-03ENEOS MATERIALS CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380042249.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-26
Filing Date
2023-03-30
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing liquid crystal polyester resin cannot effectively reduce the dielectric loss tangent under high-frequency signals, resulting in a decrease in signal quality and insufficient dimensional stability, which cannot meet the needs of high-frequency electronic equipment.

Method used

By using more than 90 mol% of aromatic hydroxycarboxylic acid structural units in the liquid crystal polyester resin and adjusting their composition ratio, including para-hydroxybenzoic acid, 6-hydroxy-2-naphtholic acid and other hydroxycarboxylic acid units, the media is optimized The tangent, anisotropy and melt viscosity of the electrical loss are prepared to produce a resin with low dielectric loss tangent and excellent dimensional stability.

Benefits of technology

It realizes reducing the dielectric loss tangent under high-frequency band signals, improving the dimensional stability of molded products, preventing signal quality from being reduced, and improving heat resistance and mechanical strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005147848160000091
    Figure BDA0005147848160000091
  • Figure BDA0005147848160000092
    Figure BDA0005147848160000092
  • Figure BDA0005147848160000201
    Figure BDA0005147848160000201
Patent Text Reader

Abstract

[Problem] To provide a liquid crystal polyester resin having a low dielectric loss tangent and an excellent balance between heat resistance and processing stability. [Solution] This liquid crystal polyester resin is characterized in that: the liquid crystal polyester resin contains structural units derived from an aromatic hydroxycarboxylic acid in an amount of 90 mol% or more of the total structural units, and has a dielectric loss tangent of 1.0 * 10-3 or less at a measurement frequency of 10 GHz; the difference (anisotropy) between the molding shrinkage in the flow direction (MD) of the injection-molded sheet of the liquid crystal polyester resin and the molding shrinkage in the direction (TD) perpendicular to the flow direction is 1.00 or less, and the melt viscosity measured under the conditions from the melting point of the liquid crystal polyester resin to the melting point + 20 DEG C and the shear speed of 1000 / s is 25 Pa * s or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a liquid crystal polyester resin, and more particularly to a liquid crystal polyester resin having a low dielectric loss tangent, a molded article containing the liquid crystal polyester resin, and an electric or electronic component having the molded article. Background Art

[0002] In recent years, with the increase in the amount of information communication in the communication field, the use of signals with high-frequency bands has increased in electronic equipment, communication equipment, etc., especially signals with frequencies of 10 9 The use of signals with frequencies in the gigahertz (GHz) band above Hz is the most popular. For example, high frequencies in the GHz band can be used in the automotive field. Specifically, millimeter-wave radars and quasi-millimeter-wave radars used to prevent automobile collisions use high frequencies of 76 to 79 GHz and 24 GHz, respectively, and are expected to become more popular in the future.

[0003] However, as the frequency of the signal used increases, it may lead to the misidentification of intelligence and the reduction of the quality of the output signal, that is, the transmission loss will increase. The transmission loss is composed of the conductor loss caused by the conductor and the dielectric loss caused by the insulating resin of the electrical and electronic components such as the substrate in the electronic equipment and communication equipment. The conductor loss is proportional to the 0.5 power of the frequency used, and the dielectric loss is proportional to the 1 power of the frequency. Therefore, in the high frequency band, especially the GHz band, the influence caused by the dielectric loss is very large. In addition, the dielectric loss increases proportionally to the dielectric loss tangent of the resin. Therefore, in order to prevent the degradation of intelligence, a resin with a low dielectric loss tangent is required.

[0004] Furthermore, resins constituting electrical and electronic components are also required to have heat resistance and moldability, etc. For example, Patent Document 1 proposes a wholly aromatic polyester resin as a polyester resin having excellent heat resistance and moldability, which contains a structural unit derived from 6-hydroxy-2-naphthoic acid at a specific composition ratio of 40 to 75 mol%, a structural unit derived from terephthalic acid at a specific composition ratio of 8.5 to 30 mol%, a structural unit derived from 4,4'-dihydroxybiphenyl at a specific composition ratio of 8.5 to 30 mol%, and a structural unit derived from p-hydroxybenzoic acid at a specific composition ratio of 0.1 to 8 mol%.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2002-179776 Summary of the invention

[0008] However, the present inventors have found that even when the wholly aromatic polyester resin proposed in Patent Document 1 is used, a liquid crystal polyester resin having a sufficiently low dielectric loss tangent and excellent dimensional stability cannot be obtained.

[0009] Therefore, the present inventors conducted intensive studies to solve the above-mentioned problems, and found that by adjusting specific properties (dielectric loss tangent, anisotropy, melt viscosity) or the composition ratio of specific structural units in a liquid crystal polyester resin composed of structural units derived from aromatic hydroxycarboxylic acids containing 90 mol % or more of the total structural units, a liquid crystal polyester resin having a low dielectric loss tangent and excellent dimensional stability can be obtained.

[0010] Therefore, an object of the present invention is to provide a liquid crystal polyester resin having a low dielectric loss tangent and excellent dimensional stability. In addition, another object of the present invention is to provide a molded article containing the liquid crystal polyester resin and an electric or electronic component having the molded article.

[0011] That is, according to the present invention, the following inventions can be provided.

[0012] [1] A liquid crystal polyester resin, characterized in that: it contains structural units derived from aromatic hydroxycarboxylic acid in an amount of 90 mol % or more of the total structural units, and

[0013] The dielectric loss tangent at a measured frequency of 10 GHz is 1.0×10 -3 the following,

[0014] The difference (anisotropy) between the mold shrinkage in the flow direction (MD) and the direction perpendicular to the flow direction (TD) of the injection molded sheet of the liquid crystal polyester resin is 1.00 or less,

[0015] The melt viscosity of the liquid crystal polyester resin measured under the conditions of the melting point to the melting point + 20° C. and a shear rate of 1000 / s is 25 Pa·s or more.

[0016] [2] A liquid crystal polyester resin, characterized in that: it contains structural units derived from aromatic hydroxycarboxylic acid in an amount of 90 mol % or more of the total structural units, and

[0017] comprising a structural unit (A) derived from p-hydroxybenzoic acid, a structural unit (B) derived from 6-hydroxy-2-naphthoic acid, and a structural unit (C) derived from a hydroxycarboxylic acid other than the above structural units (A) and (B),

[0018] The composition ratio (mol %) of the above structural units (A) to (C) satisfies the following conditions:

[0019] 10 mol%≤Structural unit (A)≤35 mol%

[0020] 50 mol%≤Structural unit (B)≤85 mol%

[0021] 0.01 mol%≤structural unit (C)<15 mol%.

[0022] [3] The liquid crystal polyester resin according to [2], wherein the structural unit (C) is a structural unit derived from at least one selected from 4'-hydroxy-4-biphenylcarboxylic acid, 6-hydroxynicotinic acid, m-hydroxybenzoic acid, 4-hydroxy-3-methylbenzoic acid, 2-fluoro-4-hydroxybenzoic acid, 4-acetamidobenzoic acid, 4-(4-hydroxyphenoxy)benzoic acid, and coumaric acid.

[0023] [4] The liquid crystal polyester resin according to [2], wherein the structural unit (C) is a structural unit derived from at least one selected from 4'-hydroxy-4-biphenylcarboxylic acid, 6-hydroxynicotinic acid, and m-hydroxybenzoic acid.

[0024] [5] The liquid crystal polyester resin according to any one of [2] to [4], further comprising at least one selected from a structural unit (D) derived from an aromatic diol and a structural unit (E) derived from an aromatic dicarboxylic acid.

[0025] [6] The liquid crystal polyester resin according to any one of [1] to [5], which has a melting point of 280° C. or higher.

[0026] [7] The liquid crystal polyester resin according to any one of [1] to [6], wherein the temperature difference between the melting point and the crystallization point is 30° C. or more.

[0027] [8] A fibrous molded article comprising the liquid crystal polyester resin according to any one of [1] to [7].

[0028] [9] A sheet-like molded article comprising the liquid crystal polyester resin according to any one of [1] to [7].

[0029]

[10] An injection-molded article comprising the liquid crystal polyester resin according to any one of [1] to [7].

[0030]

[11] An electric or electronic component comprising the molded article described in [8].

[0031]

[12] An electric or electronic component comprising the molded article described in [9].

[0032]

[13] An electric or electronic component comprising the molded article described in

[10] .

[0033] According to the present invention, a liquid crystal polyester resin having a low dielectric loss tangent and excellent dimensional stability can be realized. By using the liquid crystal polyester resin of the present invention, the dimensional stability of the produced molded product can be improved. Therefore, when the product is processed and molded, the quality of the output signal of an electrical or electronic device or a communication device using a high-frequency signal can be prevented from being reduced. DETAILED DESCRIPTION

[0034] (Liquid crystal polyester resin)

[0035] The liquid crystal polyester resin of the present invention contains 90 mol% or more of the structural units derived from aromatic hydroxycarboxylic acid in the total structural units. In the present invention, by satisfying the following first embodiment and / or second embodiment, a liquid crystal polyester resin having a low dielectric loss tangent and excellent dimensional stability can be obtained.

[0036] (First embodiment)

[0037] In the first embodiment of the present invention, the liquid crystal polyester resin is characterized by having the following specific properties (dielectric loss tangent, anisotropy, and melt viscosity).

[0038] The upper limit value of the dielectric loss tangent of the liquid crystal polyester resin of the present invention at a measurement frequency of 10 GHz is 1.0×10 -3 Below, preferably 0.95×10 -3 Below, more preferably 0.90×10 -3 Below, more preferably 0.85×10 -3 By setting the dielectric loss tangent of the liquid crystal polyester resin of the present invention to the above numerical range, a molded product having a low dielectric loss tangent can be produced, so that when the molded product is used, the quality of the output signal of an electrical or electronic device or a communication device using a high-frequency signal can be prevented from being reduced.

[0039] In this specification, the dielectric loss tangent of the liquid crystal polyester resin at 10 GHz can be measured by a separated dielectric resonator method (SPDR method) using a network analyzer N5247A manufactured by Keysight Technology Co., Ltd. or the like.

[0040] The upper limit of the absolute value of the difference (anisotropy) of the mold shrinkage rate between the flow direction (MD) and the direction (TD) perpendicular to the flow direction of the injection molded sheet of the liquid crystal polyester resin of the present invention is 1.00 or less, preferably 0.99 or less, and more preferably 0.98 or less. By setting the anisotropy of the liquid crystal polyester resin of the present invention to the above numerical range, the dimensional stability of the molded product made using the liquid crystal polyester resin can be improved.

[0041] It should be noted that in this specification, the anisotropy of the liquid crystal polyester resin is calculated based on the difference in molding shrinkage (molding shrinkage of TD - molding shrinkage of MD) calculated from the measurement results of the molding shrinkage (%) of the MD and TD of a 50 mm × 50 mm × 1 mm flat test piece obtained by heating and melting the liquid crystal polyester resin at the melting point to the melting point + 20°C.

[0042] The lower limit of the melt viscosity of the liquid crystal polyester resin of the present invention measured under the conditions of melting point to melting point + 20°C and shear rate (1000 / s) is 25Pa·s or more, preferably 30Pa·s or more, more preferably 35Pa·s or more, further preferably 40Pa·s or more, and further preferably 45Pa·s or more. In addition, the upper limit is preferably 1000Pa·s or less, more preferably 700Pa·s or less, and further preferably 250Pa·s or less. By setting the melt viscosity of the liquid crystal polyester resin of the present invention to the above-mentioned numerical range, the dielectric loss tangent can be further reduced, and the mechanical strength of the molded product can be further improved.

[0043] In addition, in this specification, the viscosity of a liquid crystal polyester resin can be measured using a capillary rheometer viscometer in accordance with JIS K7199.

[0044] (Second embodiment)

[0045] In the second embodiment of the present invention, the liquid crystal polyester resin is characterized by comprising a structural unit (A) derived from p-hydroxybenzoic acid, a structural unit (B) derived from 6-hydroxy-2-naphthoic acid, and a structural unit (C) derived from a hydroxycarboxylic acid other than the structural units (A) and (B), and

[0046] The composition ratio (mol %) of the above structural units (A) to (C) satisfies the following conditions:

[0047] 10 mol%≤Structural unit (A)≤35 mol%

[0048] 50 mol%≤Structural unit (B)≤85 mol%

[0049] 0.01 mol%≤structural unit (C)<15 mol%.

[0050] The composition ratio (mol %) of the structural units (A) to (C) of the liquid crystal polyester resin of the present invention preferably satisfies the following conditions:

[0051] 15 mol%≤Structural unit (A)≤33 mol%

[0052] 55 mol%≤Structural unit (B)≤84 mol%

[0053] 0.05 mol%≤structural unit (C)≤13 mol%;

[0054] More preferably, the following conditions are met:

[0055] 18 mol%≤Structural unit (A)≤30 mol%

[0056] 60 mol%≤Structural unit (B)≤81 mol%

[0057] 0.1 mol%≤structural unit (C)≤10 mol%;

[0058] It is further preferred to meet the following conditions:

[0059] 19 mol%≤Structural unit (A)≤29 mol%

[0060] 63 mol%≤Structural unit (B)≤80 mol%

[0061] 0.5 mol%≤structural unit (C)≤9 mol%;

[0062] The following conditions are particularly preferably met:

[0063] 20 mol%≤Structural unit (A)≤28 mol%

[0064] 65 mol%≤Structural unit (B)≤78 mol%

[0065] 1 mol%≤structural unit (C)≤8 mol%.

[0066] Furthermore, when the liquid crystal polyester resin of the present invention contains the following structural units (D) and (E) in addition to the structural units (A) to (C), the composition ratio (mol %) of the structural units (A) to (E) preferably satisfies the following conditions:

[0067] 15 mol%≤Structural unit (A)≤33 mol%

[0068] 55 mol%≤Structural unit (B)≤84 mol%

[0069] 0.05 mol%≤Structural unit (C)≤13 mol%

[0070] 0.01≤[structural unit (D)+structural unit (E)]≤3 mol%;

[0071] More preferably, the following conditions are met:

[0072] 18 mol%≤Structural unit (A)≤30 mol%

[0073] 60 mol%≤Structural unit (B)≤81 mol%

[0074] 0.1 mol%≤Structural unit (C)≤10 mol%

[0075] 0.01≤[structural unit (D)+structural unit (E)]≤3 mol%;

[0076] It is further preferred to meet the following conditions:

[0077] 19 mol%≤Structural unit (A)≤29 mol%

[0078] 63 mol%≤Structural unit (B)≤80 mol%

[0079] 0.5 mol%≤Structural unit (C)≤9 mol%

[0080] 0.05 mol%≤[structural unit (D)+structural unit (E)]≤2 mol%;

[0081] The following conditions are particularly preferably met:

[0082] 20 mol%≤Structural unit (A)≤28 mol%

[0083] 65 mol%≤Structural unit (B)≤78 mol%

[0084] 1 mol%≤Structural unit (C)≤8 mol%

[0085] 0.1 mol%≤[structural unit (D)+structural unit (E)]≤1 mol%.

[0086] Furthermore, the liquid crystal polyester resin of the second embodiment preferably has the specific properties (dielectric loss tangent, melting point, anisotropy, melt viscosity) described in the first embodiment.

[0087] Furthermore, the liquid crystal polyester resin of the first embodiment and the second embodiment preferably has the following specific properties (melting point, temperature difference between the melting point and the crystallization point).

[0088] The lower limit of the melting point of the liquid crystal polyester resin of the present invention is not particularly limited, and in view of heat resistance, the melting point is generally required to be 250°C or above. The lower limit is preferably 280°C or above, more preferably 290°C or above, further preferably 300°C or above, and further preferably 305°C or above, and the upper limit is preferably 340°C or below, more preferably 335°C or below, and further preferably 330°C or below. By setting the melting point of the liquid crystal polyester resin of the present invention to the above numerical range, the heat resistance of the molded product made using the liquid crystal polyester resin to heating processing can be improved.

[0089] The lower limit of the crystallization point of the liquid crystal polyester resin of the present invention is preferably 230°C or higher, more preferably 235°C or higher, further preferably 240°C or higher, and further preferably 245°C or higher, and the upper limit is preferably 300°C or lower, more preferably 295°C or lower, further preferably 290°C or lower, and further preferably 285°C or lower.

[0090] The lower limit of the temperature difference between the melting point and the crystallization point of the liquid crystal polyester resin of the present invention (= "melting point (°C)" - "crystallization point (°C)") is preferably 30°C or more, more preferably 35°C or more, and further preferably 40°C or more, and the upper limit is preferably 70°C or less, more preferably 65°C or less, and further preferably 60°C or less. By setting the temperature difference between the melting point and the crystallization point of the liquid crystal polyester resin of the present invention to the above numerical range, when the liquid crystal polyester is melt-molded, the liquid crystal polyester can undergo sufficient time from melting to solidification, and the degree of freedom in setting temperature conditions such as molding temperature can be increased.

[0091] It should be noted that in this specification, the melting point and crystallization point of the liquid crystal polyester resin are values ​​measured by a differential scanning calorimeter (DSC). Specifically, after the liquid crystal polyester resin is completely melted by heating from room temperature to 340-360°C at a heating rate of 10°C / min, the top of the exothermic peak obtained when the temperature is lowered to 30°C at a rate of 10°C / min is set as the crystallization point (Tc), and the top of the endothermic peak obtained when the temperature is further raised to 360°C at a rate of 10°C / min is set as the melting point (Tm).

[0092] The liquid crystallinity of the liquid crystal polyester resin of the present invention can be confirmed by heating and melting the liquid crystal polyester resin on a microscope heating stage using a polarizing microscope (trade name: BH-2) manufactured by Olympus Corporation equipped with a microscope heating stage (trade name: FP82HT) manufactured by Mettler, and then observing the presence or absence of optical anisotropy.

[0093] Hereinafter, each structural unit contained in the liquid crystal polyester resin of the present invention will be described in detail.

[0094] (Structural unit (A) derived from aromatic hydroxycarboxylic acid)

[0095] The structural unit (A) derived from an aromatic hydroxycarboxylic acid is a structural unit derived from p-hydroxybenzoic acid (HBA). Examples of the monomer that provides the structural unit (A) include p-hydroxybenzoic acid and its acetylated products, ester derivatives, and acid halides.

[0096] The composition ratio (mol%) of the structural unit (A) in the liquid crystal polyester resin is preferably 10 mol% to 30 mol%. From the viewpoint of reducing the dielectric loss tangent of the liquid crystal polyester resin and improving the dimensional stability, the lower limit of the composition ratio (mol%) of the structural unit (A) is preferably 15 mol% or more, more preferably 18 mol% or more, further preferably 19 mol% or more, and further preferably 20 mol% or more, and the upper limit is preferably 33 mol% or less, more preferably 30 mol% or less, further preferably 29 mol% or less, and further preferably 28 mol% or less.

[0097] (Structural unit (B) derived from aromatic hydroxycarboxylic acid)

[0098] The structural unit (B) derived from an aromatic hydroxycarboxylic acid is a structural unit derived from 6-hydroxy-2-naphthoic acid (HNA). Examples of the monomer that provides the structural unit (B) include 6-hydroxy-2-naphthoic acid, and its acetylated product, ester derivative, and acid halide.

[0099] The composition ratio (mol%) of the structural unit (B) in the liquid crystal polyester resin is preferably 50 mol% to 85 mol%. From the viewpoint of reducing the dielectric loss tangent of the liquid crystal polyester resin and improving the dimensional stability, the lower limit of the composition ratio (mol%) of the structural unit (B) is preferably 55 mol% or more, more preferably 60 mol% or more, further preferably 63 mol% or more, and further preferably 65 mol% or more, and the upper limit is preferably 84 mol% or less, more preferably 81 mol% or less, further preferably 80 mol% or less, and further preferably 78 mol% or less.

[0100] (Structural unit (C) derived from aromatic hydroxycarboxylic acid)

[0101] The structural unit (C) derived from an aromatic hydroxycarboxylic acid is not particularly limited, as long as it is a structural unit derived from a hydroxycarboxylic acid other than the structural units (A) and (B). The structural unit (C) is preferably, for example, a structural unit derived from at least one selected from 4'-hydroxy-4-biphenylcarboxylic acid, 6-hydroxynicotinic acid, m-hydroxybenzoic acid, 4-hydroxy-3-methylbenzoic acid, 2-fluoro-4-hydroxybenzoic acid, 4-acetamidebenzoic acid, 4-(4-hydroxyphenoxy)benzoic acid, and coumaric acid. Among them, 4'-hydroxy-4-biphenylcarboxylic acid, 6-hydroxynicotinic acid, and m-hydroxybenzoic acid are more preferred. As monomers that impart structural unit (C), there can be mentioned: their monomers, and their acetylated products, ester derivatives, acyl halides, etc.

[0102] The composition ratio (mol%) of the structural unit (C) in the liquid crystal polyester resin is preferably 0.01 mol% or more and less than 15 mol%. From the viewpoint of reducing the dielectric loss tangent of the liquid crystal polyester resin and improving the dimensional stability, the lower limit of the composition ratio (mol%) of the structural unit (C) is preferably 0.05 mol% or more, more preferably 0.1 mol% or more, further preferably 0.5 mol% or more, and further preferably 1 mol% or more, and the upper limit is preferably 13 mol% or less, more preferably 10 mol% or less, further preferably 9 mol% or less, and further preferably 8 mol% or less.

[0103] (Structural unit (D) derived from aromatic diol)

[0104] The liquid crystal polyester resin of the present invention may further include a structural unit (D) derived from an aromatic diol. The structural unit (D) derived from an aromatic diol is preferably a structural unit derived from an aromatic diol represented by the following formula (1). It should be noted that the structural unit (D) may include only one type or two or more types.

[0105] [Chemical formula 1]

[0106]

[0107] In the above formula, Ar 2 It is a divalent hydrocarbon group having an aromatic ring which may have a substituent as required. Examples of the hydrocarbon group having an aromatic ring include phenyl, biphenyl, 4,4'-isopropylidene diphenyl, naphthyl, anthracenyl, and phenanthryl. Examples of the substituent include hydrogen, alkyl, alkoxy, and fluorine. The number of carbon atoms in the alkyl group is preferably 1 to 10, and more preferably 1 to 5. In addition, it may be a linear alkyl group or a branched alkyl group. The number of carbon atoms in the alkoxy group is preferably 1 to 10, and more preferably 1 to 5.

[0108] Examples of the monomer that provides the structural unit (D) include 4,4-dihydroxybiphenyl (BP), hydroquinone (HQ), methylhydroquinone (MeHQ), 4,4′-isopropylidene diphenol (BisPA), and acylates, ester derivatives, and acyl halides thereof.

[0109] (Structural unit (E) derived from aromatic dicarboxylic acid)

[0110] The liquid crystal polyester resin of the present invention may further include a structural unit (E) derived from an aromatic dicarboxylic acid. It may also further include a structural unit (D) derived from an aromatic diol. The structural unit (E) derived from an aromatic dicarboxylic acid is preferably a structural unit derived from an aromatic dicarboxylic acid represented by the following formula (2). It should be noted that the structural unit (E) may include only one type or may include two or more types.

[0111] [Chemical formula 2]

[0112]

[0113] In the above formula, Ar 3 It is a divalent hydrocarbon group having an aromatic ring which may have a substituent as required. Examples of the hydrocarbon group having an aromatic ring include phenyl, biphenyl, 4,4'-isopropylidene diphenyl, naphthyl, anthracenyl, and phenanthryl. Examples of the substituent include hydrogen, alkyl, alkoxy, and fluorine. The number of carbon atoms in the alkyl group is preferably 1 to 10, and more preferably 1 to 5. In addition, it may be a linear alkyl group or a branched alkyl group. The number of carbon atoms in the alkoxy group is preferably 1 to 10, and more preferably 1 to 5.

[0114] Examples of the monomer that provides the structural unit (E) include terephthalic acid (TPA), isophthalic acid (IPA), 2,6-naphthalene dicarboxylic acid (NADA), and acylates, ester derivatives, and acyl halides thereof.

[0115] The total composition ratio (mol%) of the structural unit (D) and the structural unit (E) in the liquid crystal polyester resin is preferably 0.01 mol% to 3 mol%. From the viewpoint of reducing the dielectric loss tangent and improving the dimensional stability of the liquid crystal polyester resin, the lower limit of the total composition ratio (mol%) of the structural unit (D) and the structural unit (E) is preferably 0.05 mol% or more, more preferably 0.1 mol% or more, and the upper limit is preferably 2 mol% or less, more preferably 1 mol% or less.

[0116] (Method for producing liquid crystal polyester resin)

[0117] The liquid crystal polyester resin of the present invention can be produced by the following method (two-stage polymerization), which includes: a step of subjecting a monomer imparting structural units (A) to (C) and at least one of a monomer imparting structural unit (D) and a monomer imparting structural unit (E) included as required to melt polymerize to obtain a polymer; and a step of subjecting the above polymer to solid phase polymerization to obtain a liquid crystal polyester resin.

[0118] From the viewpoint of efficiently obtaining a liquid crystal polyester resin, the melt polymerization is preferably carried out under reflux of acetic acid in the presence of 1.03 to 1.15 molar equivalents of anhydride based on all hydroxyl groups in all monomers.

[0119] The reaction temperature of the melt polymerization is preferably in the temperature range of the melting point to (melting point + 70)°C, more preferably in the temperature range of (melting point + 20)°C to (melting point + 50)°C.

[0120] Melt polymerization is preferably carried out in the presence of a catalyst and in the absence of a solvent. As the catalyst, a catalyst known as a catalyst for polymerization of a polymer can be used. Examples of the catalyst include metal salt catalysts such as potassium acetate, magnesium acetate, stannous acetate, lead acetate, sodium acetate, tetrabutyl titanate, and antimony trioxide; organic compound catalysts such as nitrogen-containing heterocyclic compounds such as N-methylimidazole, etc. The amount of the catalyst used is not particularly limited, and is preferably the total molar number of the monomers × (10 to 100) mg / mole.

[0121] When solid phase polymerization is performed, the polymer obtained by melt polymerization can be cooled and solidified and then crushed to form a powder or flake. In addition, the polymer strands obtained by melt polymerization can be granulated to form particles. The reaction temperature of solid phase polymerization is preferably below the melting point, preferably (melting point - 30) ° C to (melting point - 10) ° C. Solid phase polymerization can be performed while stirring, or it can be performed in a static state without stirring.

[0122] The polymerization reaction apparatus is not particularly limited, and is preferably a reaction apparatus used in a reaction using a general high-viscosity fluid. Examples of these reaction apparatuses include, for example, a stirring tank type polymerization reaction apparatus having a stirring device with stirring blades of anchor type, multi-stage type, spiral ribbon type, spiral shaft type, or various shapes of these deformations, or a mixing apparatus commonly used for resin mixing, such as a kneader, a roll crusher, and a Banbury mixer.

[0123] (Molding products)

[0124] The molded article of the present invention contains a liquid crystal polyester resin and may further contain a filler.

[0125] (Bulking Agent)

[0126] Examples of fillers include carbon fiber, graphite, glass fiber, talc, mica, glass flakes, clay, sericite, calcium carbonate, calcium sulfate, calcium silicate, silicon dioxide, aluminum oxide, aluminum hydroxide, calcium hydroxide, graphite, potassium titanate, titanium oxide, fluorocarbon resin fiber, fluorocarbon resin, barium sulfate, various whiskers, etc. These fillers may be used alone or in combination of two or more.

[0127] Relative to the total amount of the molded product, the content of the filler in the molded product is preferably 1% to 70% by mass, more preferably 5% to 60% by mass, further preferably 10% to 50% by mass, and further preferably 15% to 45% by mass. In the case of containing two or more fillers, it is preferred that their total content is within the above range. If the content of the filler in the molded product is within the above range, a molded product with better mechanical properties is obtained, so it is preferred.

[0128] (Other resins)

[0129] The molded article of the present invention may also contain other resins other than liquid crystal polyester resins within the scope of the present invention. As other resins, for example, polyester resins such as polyethylene terephthalate, polyethylene naphthalate, polyarylate, polycyclohexane dimethyl terephthalate, and polybutylene terephthalate; polyolefin resins such as polyethylene and polypropylene; ethylene resins such as cycloolefin polymers and polyvinyl chloride; (meth) acrylic resins such as polyacrylates, polymethacrylates, and polymethyl methacrylate; polyphenylene ether resins; polyacetal resins; polyamide resins; imide resins such as polyimide and polyetherimide; polystyrene resins such as polystyrene, high impact polystyrene, AS resin, and ABS resin; thermosetting resins such as epoxy resins; cellulose resins, polyetheretherketone resins, fluororesins, and polycarbonate resins. These other resins can be used alone or in combination.

[0130] The upper limit of the content of the resin other than the liquid crystal polyester resin in the molded article is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, relative to 100 parts by mass of the liquid crystal polyester resin.

[0131] (Other additives)

[0132] The molded article of the present invention may further contain other additives, such as colorants, dispersants, plasticizers, antioxidants, curing agents, flame retardants, heat stabilizers, ultraviolet absorbers, antistatic agents, and surfactants, without departing from the scope of the present invention. These other additives may be used alone or in combination of two or more.

[0133] The shape of the molded article can be appropriately changed according to the application and is not particularly limited. Examples of the shape of the molded article include a fiber shape, a plate shape, a sheet shape, and a rod shape.

[0134] The molded article of the present invention can be produced by a known molding method using a resin composition containing a liquid crystal polyester resin and a filler or other resins as required. The molding method can be, for example, any method such as melt spinning, solution spinning, injection molding, compression molding, injection compression molding, calendaring, punching, etc.

[0135] (Electrical and electronic components)

[0136] The electrical and electronic component of the present invention comprises a molded product (e.g., a fiber-shaped molded product or an injection molded product, etc.) containing a liquid crystal polyester resin. Examples of the electrical and electronic component comprising the above-mentioned molded product include electronic devices such as ETC, GPS, wireless LAN, and mobile phones, antennas used in communication devices, connectors for high-speed transmission, CPU sockets, circuit substrates, flexible printed substrates (FPCs), laminated circuit substrates, millimeter wave and quasi-millimeter wave radars such as collision avoidance radars, RFID tags, capacitors, inverter components, cable coating materials, insulating materials for secondary batteries such as lithium-ion batteries, and speaker diaphragms.

[0137] Example

[0138] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to the Examples.

[0139] <Manufacturing of Liquid Crystal Polyester Resin>

[0140] (Example 1)

[0141] 25 mol % of p-hydroxybenzoic acid (HBA), 73 mol % of 6-hydroxy-2-naphthoic acid (HNA), and 2 mol % of 4'-hydroxy-4-biphenylcarboxylic acid (C1) were added to a polymerization container with a stirring blade, and potassium acetate was added as a catalyst. After the polymerization container was decompressed and nitrogen was injected three times, acetic anhydride (1.05 molar equivalents relative to the hydroxyl group) was added, the temperature was raised to 150°C, and an acetylation reaction was carried out under reflux for 2 hours.

[0142] After the acetylation is completed, the polymerization container in which acetic acid is distilled is heated at 0.5°C / min until the temperature of the melting zone in the tank reaches 310°C. Thereafter, the polymer is extracted and cooled to solidify. The obtained polymer is crushed to a size that can pass through a sieve with a mesh of 2.0 mm to obtain a polymer. Next, the obtained polymer is heated in an oven manufactured by YamatoScientific Co., Ltd., and the temperature is raised from room temperature to 300°C, and then maintained for 2 hours for solid phase polymerization.

[0143] Thereafter, the polymer was allowed to naturally release heat at room temperature to obtain the polyester resin of the present invention. The polyester resin was heated and melted on the microscope heating stage using a polarizing microscope (trade name: BH-2) manufactured by Olympus Corporation equipped with a microscope heating stage (trade name: FP82HT) manufactured by Mettler, and liquid crystallinity was confirmed by the presence or absence of optical anisotropy.

[0144] (Example 2)

[0145] A polyester resin was obtained in the same manner as in Example 1 except that the monomer addition was changed to 25 mol% HBA, 73 mol% HNA, 1 mol% 4'-hydroxy-4-biphenylcarboxylic acid (C1), and 1 mol% 6-hydroxynicotinic acid (C2). Next, the liquid crystallinity of the polyester resin was confirmed in the same manner as above.

[0146] (Example 3)

[0147] A polyester resin was obtained in the same manner as in Example 1 except that the monomer addition was changed to 22 mol % of HBA, 73 mol % of HNA, and 5 mol % of 4'-hydroxy-4-biphenylcarboxylic acid (C1). Next, the liquid crystallinity of the polyester resin was confirmed in the same manner as above.

[0148] (Example 4)

[0149] A polyester resin was obtained in the same manner as in Example 1 except that the monomer addition was changed to 25 mol % of HBA, 73 mol % of HNA, and 2 mol % of 4-hydroxy-3-methylbenzoic acid (C3). Next, the liquid crystallinity of the polyester resin was confirmed in the same manner as above.

[0150] (Example 5)

[0151] A polyester resin was obtained in the same manner as in Example 1 except that the monomer addition was changed to 25 mol % of HBA, 73 mol % of HNA, and 2 mol % of 2-fluoro-4-hydroxybenzoic acid (C4). Next, the liquid crystallinity of the polyester resin was confirmed in the same manner as above.

[0152] (Example 6)

[0153] A polyester resin was obtained in the same manner as in Example 1 except that the monomer addition was changed to 28 mol% HBA, 69 mol% HNA, 2 mol% 4'-hydroxy-4-biphenylcarboxylic acid (C1), and 1 mol% m-hydroxybenzoic acid (C5). Next, the liquid crystallinity of the polyester resin was confirmed in the same manner as above.

[0154] (Example 7)

[0155] A polyester resin was obtained in the same manner as in Example 1 except that the monomer addition was changed to 25 mol % of HBA, 73 mol % of HNA, and 2 mol % of 4-(4-hydroxyphenoxy)benzoic acid (C6). Next, the liquid crystallinity of the polyester resin was confirmed in the same manner as above.

[0156] (Example 8)

[0157] A polyester resin was obtained in the same manner as in Example 1 except that the monomer addition was changed to 19 mol % of HBA, 73 mol % of HNA, and 8 mol % of 4'-hydroxy-4-biphenylcarboxylic acid (C1). Next, the liquid crystallinity of the polyester resin was confirmed in the same manner as above.

[0158] (Example 9)

[0159] A polyester resin was obtained in the same manner as in Example 1 except that the monomer addition was changed to 26.5 mol % of HBA, 73 mol % of HNA, and 0.5 mol % of 4'-hydroxy-4-biphenylcarboxylic acid (C1). Next, the liquid crystallinity of the polyester resin was confirmed in the same manner as above.

[0160] (Example 10)

[0161] A polyester resin was obtained in the same manner as in Example 1 except that the monomer addition was changed to 25 mol % of HBA, 73 mol % of HNA, and 2 mol % of coumaric acid (C7). Next, the liquid crystallinity of the polyester resin was confirmed in the same manner as above.

[0162] (Example 11)

[0163] A polyester resin was obtained in the same manner as in Example 1 except that the monomer addition was changed to 24.9 mol % of HBA, 72.6 mol % of HNA, 2 mol % of 4'-hydroxy-4-biphenylcarboxylic acid (C1), and 0.5 mol % of terephthalic acid (TPA). Next, the liquid crystallinity of the polyester resin was confirmed in the same manner as above.

[0164] (Example 12)

[0165] A polyester resin was obtained in the same manner as in Example 1 except that the monomer addition was changed to 24.9 mol % of HBA, 72.6 mol % of HNA, 2 mol % of 6-hydroxynicotinic acid (C2), and 0.5 mol % of TPA. Next, the liquid crystallinity of the polyester resin was confirmed in the same manner as above.

[0166] (Example 13)

[0167] A polyester resin was obtained in the same manner as in Example 1 except that the monomer addition was changed to 25 mol % of HBA, 73 mol % of HNA, and 2 mol % of m-hydroxybenzoic acid (C5). Next, the liquid crystallinity of the polyester resin was confirmed in the same manner as above.

[0168] (Example 14)

[0169] A polyester resin was obtained in the same manner as in Example 1 except that the monomer addition was changed to 19 mol % of HBA, 73 mol % of HNA, and 8 mol % of 6-hydroxynicotinic acid (C2). Next, the liquid crystallinity of the polyester resin was confirmed in the same manner as above.

[0170] (Comparative Example 1)

[0171] A polyester resin was obtained in the same manner as in Example 1 except that the monomer addition was changed to 73 mol % of HBA and 27 mol % of HNA. Next, the liquid crystallinity of the polyester resin was confirmed in the same manner as above.

[0172] (Comparative Example 2)

[0173] A polyester resin was obtained in the same manner as in Example 1 except that the monomer addition was changed to 60 mol % of HBA, 20 mol % of 4,4′-dihydroxybiphenyl (BP), 15 mol % of TPA, and 5 mol % of isophthalic acid (IPA). Next, the liquid crystallinity of the polyester resin was confirmed in the same manner as above.

[0174] (Comparative Example 3)

[0175] A polyester resin was obtained in the same manner as in Example 1 except that the monomer addition was changed to 6 mol % of HBA, 40 mol % of HNA, 27 mol % of BP, and 27 mol % of 2,6-naphthalenedicarboxylic acid (NADA). Next, the liquid crystallinity of the polyester resin was confirmed in the same manner as above.

[0176] (Comparative Example 4)

[0177] A polyester resin was obtained in the same manner as in Example 1 except that the monomer addition was changed to 35 mol % of HBA, 50 mol % of HNA, and 15 mol % of 4-acetamidebenzoic acid (C8). Next, the liquid crystallinity of the polyester resin was confirmed in the same manner as above.

[0178] (Comparative Example 5)

[0179] A polyester resin was obtained in the same manner as in Example 1 except that the monomer addition was changed to 20 mol % of HBA, 73 mol % of HNA, and 7 mol % of m-hydroxybenzoic acid (C5). Next, the liquid crystallinity of the polyester resin was confirmed in the same manner as above.

[0180] (Example 15)

[0181] A polyester resin was obtained in the same manner as in Example 1 except that the monomer addition was changed to 28.9 mol % of HBA, 68.6 mol % of HNA, 2 mol % of 6-hydroxynicotinic acid (C2), and 0.5 mol % of IPA. Next, the liquid crystallinity of the polyester resin was confirmed in the same manner as above.

[0182] (Example 16)

[0183] A polyester resin was obtained in the same manner as in Example 1 except that the monomer addition was changed to 25.9 mol % of HBA, 69.6 mol % of HNA, 4 mol % of 6-hydroxynicotinic acid (C2), and 0.5 mol % of IPA. Next, the liquid crystallinity of the polyester resin was confirmed in the same manner as above.

[0184] (Example 17)

[0185] A polyester resin was obtained in the same manner as in Example 1 except that the monomer addition was changed to 24.9 mol % of HBA, 72.6 mol % of HNA, 2 mol % of 6-hydroxynicotinic acid (C2), and 0.5 mol % of IPA. Next, the liquid crystallinity of the polyester resin was confirmed in the same manner as above.

[0186] (Example 18)

[0187] A polyester resin was obtained in the same manner as in Example 1 except that the monomer addition was changed to 24.9 mol % of HBA, 72.6 mol % of HNA, 2 mol % of m-hydroxybenzoic acid (C5), and 0.5 mol % of TPA. Next, the liquid crystallinity of the polyester resin was confirmed in the same manner as above.

[0188] (Example 19)

[0189] A polyester resin was obtained in the same manner as in Example 1 except that the monomer addition was changed to 29.9 mol % of HBA, 68.6 mol % of HNA, 1 mol % of m-hydroxybenzoic acid (C5), and 0.5 mol % of TPA. Next, the liquid crystallinity of the polyester resin was confirmed in the same manner as above.

[0190] (Example 20)

[0191] A polyester resin was obtained in the same manner as in Example 1 except that the monomer addition was changed to 11.9 mol % of HBA, 79.6 mol % of HNA, 8 mol % of m-hydroxybenzoic acid (C5), and 0.5 mol % of TPA. Next, the liquid crystallinity of the polyester resin was confirmed in the same manner as above.

[0192] (Example 21)

[0193] A polyester resin was obtained in the same manner as in Example 1 except that the monomer addition was changed to 24.9 mol % of HBA, 68.6 mol % of HNA, 6 mol % of m-hydroxybenzoic acid (C5), and 0.5 mol % of TPA. Next, the liquid crystallinity of the polyester resin was confirmed in the same manner as above.

[0194] (Example 22)

[0195] A polyester resin was obtained in the same manner as in Example 1 except that the monomer addition was changed to 16.9 mol % of HBA, 74.6 mol % of HNA, 8 mol % of m-hydroxybenzoic acid (C5), and 0.5 mol % of TPA. Next, the liquid crystallinity of the polyester resin was confirmed in the same manner as above.

[0196] (Example 23)

[0197] A polyester resin was obtained in the same manner as in Example 1 except that the monomer addition was changed to 19.9 mol % of HBA, 74.6 mol % of HNA, 5 mol % of m-hydroxybenzoic acid (C5), and 0.5 mol % of TPA. Next, the liquid crystallinity of the polyester resin was confirmed in the same manner as above.

[0198] (Example 24)

[0199] A polyester resin was obtained in the same manner as in Example 1 except that the monomer addition was changed to 22.9 mol % of HBA, 71.6 mol % of HNA, 5 mol % of m-hydroxybenzoic acid (C5), and 0.5 mol % of TPA. Next, the liquid crystallinity of the polyester resin was confirmed in the same manner as above.

[0200] (Example 25)

[0201] A polyester resin was obtained in the same manner as in Example 1 except that the monomer addition was changed to 34 mol % of HBA, 65 mol % of HNA, and 1 mol % of m-hydroxybenzoic acid (C5). Next, the liquid crystallinity of the polyester resin was confirmed in the same manner as above.

[0202] (Example 26)

[0203] A polyester resin was obtained in the same manner as in Example 1 except that the monomer addition was changed to 24.9 mol % of HBA, 72.6 mol % of HNA, 2 mol % of m-hydroxybenzoic acid (C5), and 0.5 mol % of BP. Next, the liquid crystallinity of the polyester resin was confirmed in the same manner as above.

[0204] (Example 27)

[0205] A polyester resin was obtained in the same manner as in Example 1 except that the monomer addition was changed to 24.8 mol % of HBA, 72.2 mol % of HNA, 2 mol % of m-hydroxybenzoic acid (C5), and 1 mol % of HQ. Next, the liquid crystallinity of the polyester resin was confirmed in the same manner as above.

[0206] (Example 28)

[0207] A polyester resin was obtained in the same manner as in Example 1 except that the monomer addition was changed to 24.9 mol % of HBA, 72.6 mol % of HNA, 2 mol % of m-hydroxybenzoic acid (C5), and 0.5 mol % of NADA. Next, the liquid crystallinity of the polyester resin was confirmed in the same manner as above.

[0208] (Example 29)

[0209] A polyester resin was obtained in the same manner as in Example 1 except that the monomer addition was changed to 24.8 mol % of HBA, 72.2 mol % of HNA, 2 mol % of m-hydroxybenzoic acid (C5), and 1 mol % of TPA. Next, the liquid crystallinity of the polyester resin was confirmed in the same manner as above.

[0210] (Example 30)

[0211] A polyester resin was obtained in the same manner as in Example 1 except that the monomer addition was changed to 25 mol % of HBA, 72.9 mol % of HNA, 2 mol % of m-hydroxybenzoic acid (C5), and 0.1 mol % of TPA. Next, the liquid crystallinity of the polyester resin was confirmed in the same manner as above.

[0212] (Comparative Example 6)

[0213] A polyester resin was obtained in the same manner as in Example 1 except that the monomer addition was changed to 21 mol % of HBA, 77 mol % of HNA, and 2 mol % of m-hydroxybenzoic acid (C5). Next, the liquid crystallinity of the polyester resin was confirmed in the same manner as above.

[0214] <Determination of melting point and crystallization point>

[0215] The melting point and crystallization point of the liquid crystal polyester resin obtained in the examples and comparative examples were measured by a differential scanning calorimeter (DSC) manufactured by Hitachi High-Tech Science Company. First, the liquid crystal polyester resin was completely melted by heating from room temperature to 340-360°C at a heating rate of 10°C / min, and the top of the exothermic peak obtained when the temperature was lowered to 30°C at a rate of 10°C / min was set as the crystallization point (Tc), and the top of the endothermic peak obtained when the temperature was further increased to 360°C at a rate of 10°C / min was set as the melting point (Tm). In addition, the difference between the melting point and the crystallization point was calculated based on the obtained melting point and crystallization point. The melting point (Tm), the crystallization point (Tc), and the difference between the melting point and the crystallization point (Tm-Tc) are shown in Tables 1 and 2. It should be noted that unmeasured parts are recorded as "-".

[0216] According to the results in Table 1 and Table 2, the liquid crystal polyester resins of Examples 1 to 30 have low dielectric loss tangent, high melting point, excellent heat resistance, small anisotropy, and excellent dimensional stability.

[0217] <Preparation of Flat Test Specimen A>

[0218] The liquid crystal polyester resins obtained in the examples and comparative examples were heated and melted at a temperature between the melting point and the melting point + 20° C. and injection molded to prepare a flat test piece A of 30 mm×30 mm×0.4 mm.

[0219] <Preparation of Flat Test Specimen B>

[0220] The liquid crystal polyester resins obtained in the examples and comparative examples were heated and melted at a temperature between the melting point and the melting point + 20° C. and injection molded to prepare a flat test piece B of 50 mm×50 mm×1 mm.

[0221] <Measurement of dielectric loss tangent (10 GHz)>

[0222] The dielectric loss tangent (tan δ) in the plane direction of the flat plate test piece A prepared above was measured at a frequency of 10 GHz using a network analyzer N5247A from Keysight Technology by a separated pillar dielectric resonator method (SPDR method). The measurement results are shown in Tables 1 and 2. It should be noted that the unmeasured parts are marked as "-".

[0223] <Measurement of anisotropy>

[0224] The mold shrinkage (%) of the flat test piece B prepared above in the flow direction (MD) and the direction perpendicular to the flow direction (TD) was measured, and the difference in their mold shrinkage (molding shrinkage of TD - molding shrinkage of MD) was calculated to evaluate the anisotropy. The calculation results are shown in Tables 1 and 2. The smaller the difference, the smaller the anisotropy. It should be noted that the unmeasured parts are recorded as "-".

[0226] <Measurement of melt viscosity>

[0227] The melt viscosity (Pa·s) of the liquid crystal polyester resins obtained in Examples and Comparative Examples under the conditions of melting point +20°C and shear rate 1000 / s was measured using a capillary rheometer viscometer (Toyo Seiki Seisakusho Co., Ltd., Capillograph 1D) and a capillary with an inner diameter of 1 mm in accordance with JIS K7199. The measurement results are shown in Tables 1 and 2.

[0228]

[0229]

Claims

1. A liquid crystal polyester resin, characterized in that: It contains 90 mol% or more of the total structural units derived from aromatic hydroxycarboxylic acid, and The dielectric loss tangent at a measured frequency of 10 GHz is 1.0×10 -3 the following, The difference in mold shrinkage between the flow direction MD and the direction TD perpendicular to the flow direction of the injection molded sheet of the liquid crystal polyester resin, i.e., anisotropy, is 1.00 or less. The melt viscosity measured under the conditions of the melting point of the liquid crystal polyester resin to the melting point + 20° C. and a shear rate of 1000 / s is 25 Pa·s or more.

2. A liquid crystal polyester resin, characterized in that: It contains 90 mol% or more of the total structural units derived from aromatic hydroxycarboxylic acid, and comprising a structural unit (A) derived from p-hydroxybenzoic acid, a structural unit (B) derived from 6-hydroxy-2-naphthoic acid, and a structural unit (C) derived from a hydroxycarboxylic acid other than the structural units (A) and (B), The composition ratio (mol %) of the structural units (A) to (C) satisfies the following conditions: 10 mol%≤Structural unit (A)≤35 mol% 50 mol%≤Structural unit (B)≤85 mol% 0.01 mol%≤structural unit (C)<15 mol%.

3. The liquid crystal polyester resin according to claim 2, wherein The structural unit (C) is a structural unit derived from at least one selected from 4'-hydroxy-4-biphenylcarboxylic acid, 6-hydroxynicotinic acid, m-hydroxybenzoic acid, 4-hydroxy-3-methylbenzoic acid, 2-fluoro-4-hydroxybenzoic acid, 4-acetamidobenzoic acid, 4-(4-hydroxyphenoxy)benzoic acid, and coumaric acid.

4. The liquid crystal polyester resin according to claim 2, wherein The structural unit (C) is a structural unit derived from at least one selected from the group consisting of 4′-hydroxy-4-biphenylcarboxylic acid, 6-hydroxynicotinic acid, and m-hydroxybenzoic acid. The liquid crystal polyester resin according to any one of claims 2 to 4, further comprising at least one selected from a structural unit (D) derived from an aromatic diol and a structural unit (E) derived from an aromatic dicarboxylic acid. The liquid crystal polyester resin according to claim 1 or 2, which has a melting point of 280°C or higher. 7 . The liquid crystal polyester resin according to claim 6 , wherein the temperature difference between the melting point and the crystallization point is 30° C. or more. 8 . A fibrous molded article comprising the liquid crystal polyester resin according to claim 1 . 9 . A sheet-shaped molded product comprising the liquid crystal polyester resin according to claim 1 . 10 . An injection molded article comprising the liquid crystal polyester resin according to claim 1 or 2 .

11. An electric or electronic component comprising the molded article according to claim 8.

12. An electric or electronic component comprising the molded article according to claim 9. 13 . An electric or electronic component comprising the molded article according to claim 10 .